Interactive Impact of EWOM Message Characteristics and Format on Brand Evaluation and Online Brand Engagement: Towards an Integrative Framework - Alqahtani, Abdulaziz S. (Curtin University, 2023)
With the rapid rise in the popularity and usage of social media platforms and the associated sharing of electronic word of mouth (EWOM), many questions about its impact on customers’ attitudes and behaviours still need to be answered. This research aims to explore the interactive effect of message characteristics (valence and credibility) and message formats (text, picture, audio-visual and audio) on brand evaluation and online brand engagement, utilising the elaboration likelihood model (ELM) of persuasion theory.